BEYOND THE DUMP: UNMASKING THE CUMULATIVE HEALTH RISKS OF HEAVY METALS IN GROUNDWATER SAMPLES NEAR GOSA DUMPSITE, FCT, ABUJA, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Concerns about heavy metal (HM) contamination of groundwater from dumpsite leachate have global human health implications. The study assessed the concentration level of Manganese (Mn), Lead (Pb), Chromium (Cr), Cadmium (Cd), Copper (Cu) and Zinc (Zn) in the sampled well water near the Gosa dumpsite in FCT, Abuja. Water samples collected were taken to the laboratory in clean airtight plastic containers where HM analysis was performed on the water samples using atomic absorption spectroscopy (AAS) using standard procedures.  The concentrations of the HM exceeded the recommended standards for drinking water by both the World Health Organization (WHO) and Standard Organization of Nigeria (SON) except Mn that was within the WHO permissible standard but exceeded the SON permissible limit. Regular consumption of well water near the Gosa dumpsite pose a carcinogenic health risk with respect to Pb, Cr and Cd exposure via oral routes. The cumulative non-carcinogenic risk effect of the HM as indicated by the Hazard Index (HI) exceeded a value of one (HQ>1) to both groups of consumers with children having higher values compared to adults. The study recommends the need to monitor the quality of water while ensuring proactive action is taken by environmental agencies to tackle the looming threat.
Keywords: Hazard quotient; Water quality; Groundwater; Heavy metals; Carcinogenic risk